The Effect of Digitalization and Professionalism on Public Satisfaction Through Public Service Quality - M. Zahari; Mufidah Mufidah; Yanti Yanti (Dinasti Publisher, 2025)
The purpose of this study is to describe public satisfaction, professionalism, digitalization, and the quality of public services. It examines how professionalism and digitization affect public satisfaction. It examines how professionalism and digitization affect public satisfaction through the caliber of public services. The Population and Civil Registration Office of West Tanjung Jabung Regent, Jambi Province, served as the study's site. This study made use of both principal and supplemental data. 73,266 service customers made up the study's population, and a random sampling technique was used to choose 100 respondents. Descriptive and quantitative analysis were employed in this survey-based investigation. Path study with the Partial Least Squares (PLS) method was employed in the quantitative study. The findings demonstrate that public satisfaction is positively and significantly impacted by professionalism and digitization. By improving the caliber of public services, professionalism and digitalization increase public satisfaction. These findings clarify that the public's perception of service quality improves with increasing digitalization and professionalism. Ideal service The key to fulfilling the public's expectations of government services is quality. As a result, the public will gain materially from government representatives' presence, which will raise satisfaction levels.